P06 Hepatic lumican expression in paediatric non-alcoholic fatty liver disease. (16th November 2010) - Fitzpatrick, E; Mitry, R; Quaglia, A; Dhawan, A
Abstract : Introduction: Lumican is a glycoprotein involved in collagen cross-linking and modulation of the innate immune system. Overexpression of lumican was recently described in a group of adult patients with histologically progressive non-alcoholic fatty liver disease (NAFLD). It has not yet been evaluated in paediatric NAFLD. Aim: The aim of this study was to determine the degree of lumican expression in the liver of children with varying stages of NAFLD. Method: The study group consisted of 24 children (17 boys), median age 13.1 years, with liver biopsy-proven NAFLD and six children with chronic liver disease other than NAFLD (four with autoimmune hepatitis and two with Wilson disease). Paraffin-embedded biopsy sections were scored according to the NAFLD Activity Score (NAS). Sections were immuno-stained for lumican using HRP-DAB. Quantitative analysis was performed using imageJ (NIH, USA), expressing lumican staining as percentage of the total area. In addition, relative quantification real-time PCR for lumican was undertaken on frozen biopsy specimens. Results: Median BMI z-score of the group with NAFLD was 2.2 and median HOMA-IR; 4.4. 58% had splenomegaly. Thirteen children scored =5 (NASH), 6 scored 3–4 (borderline) and 5 scored=2 (simple steatosis). Fibrosis was minimal in 10 (F<2) and significant in 14 (F=2). Two children had type 1 NASH, the remainder had type 2 or a mixed pattern. Lumican was overexpressed in those with significant fibrosis (F=2) vs those with minimal fibrosis (F<2); (168%, p=0.01). Lumican was also overexpressed in NASH vs simple steatosis (215%, p=0.012). The pattern of lumican staining followed the sinusoidal contour, and marked the portal vascular endothelium and the luminal border of bile ducts. There was no clear staining of hepatocytes. At gene level, lumican was upregulated (compared to normal control liver) in those with F=2 (15.8-fold) and in those with F<2 (10.9-fold). Lumican expression was not related to age, BMI z-score, HOMA-IR, splenomegaly or transaminase levels. There was variable expression of lumican in the biopsies of those with chronic liver disease other than NAFLD. Percentage area stained did not correlate with degree of fibrosis in these patients. Conclusion: Lumican is expressed with increasing severity of paediatric NAFLD. Upregulation at gene level in those with both minimal and histologically more severe disease is also evident. The role of lumican in progression of disease has not yet been elucidated and should be the focus of further investigation.